Engineering surveys of Sri Lankan schools exposed to tsunami - Cels, Jonas; Rossetto, Tiziana; Dias, Priyan; Thamboo, Julian; Wijesundara, Kushan; Baiguera, Marco; Del Zoppo, Marta (Frontiers in Earth Science, 2023)
The 2004 Indian Ocean tsunami affected 5% of Sri Lanka’s schools, severely damaging 108 and destroying 74. The catastrophe highlighted the critical role of schools in providing educational continuity during community recovery. Sri Lanka has since rehabilitated and rebuilt most of the destroyed schools along the coastline. However, there is a limited understanding of current levels of school exposure to tsunami. This hampers preparedness and risk reduction interventions that can improve community and educational tsunami resilience. This paper presents a multi-disciplinary school exposure database relevant to both vulnerability and loss modelling. The repository includes data on 38 schools and 86 classroom buildings, surveyed across the coastal districts of Ampara, Batticaloa and Galle in Sri Lanka, which were heavily affected by the 2004 tsunami. A new engineering rapid visual survey tool is presented that was used to conduct the physical assessment of schools for the exposure repository. School damage mechanisms observed in past tsunami inform the survey forms, which are designed to capture information at both school compound and building levels. The tsunami engineering survey tools are universally applicable for the visual assessment of schools exposed to tsunami. The surveys show that most Sri Lankan school buildings can be classified into three building archetypes. This means that future risk assessments can be conducted considering a small number of index buildings that are based on these archetypes with differing partition arrangements and structural health conditions. The surveys also raise three significant concerns. Firstly, most schools affected by the 2004 tsunami remain in the same exposed locations without any consideration for tsunami design or strengthening provisions. Secondly, Sri Lankan schools are fragile to tsunami loading and many of the schools in the Galle district suffer from severe corrosion, which will further affect their tsunami vulnerability. Thirdly, schools do not appear prepared for tsunami, and do not have adequate tsunami warnings nor evacuation protocols in place. These observations raise the urgent need to mitigate tsunami risk, including a holistic plan for tsunami retrofitting and for interventions to improve the tsunami preparedness of schools in Sri Lanka.